The Prognostic Significance of the Fibrinogen-to-Albumin Ratio in Patients With Triple-Negative Breast Cancer: A Retrospective Study - Yang, Qinheng; Liang, Dong; Yu, Yang; Lv, Feng (Frontiers in Surgery, 2022)
Objective: This study aimed to investigate the potential prognostic value of fibrinogen-to-albumin ratio (FAR) in patients with triple-negative breast cancer (TNBC). Methods: This study used a retrospective design and enrolled 224 patients with TNBC treated between January 2009 and December 2014 at the Henan Provincial People’s Hospital. The receiver operating characteristic curve (ROC) was used to determine the optimal cut-off value for FAR. The associations between TNBC and clinicopathologic categorical variables by FAR were analyzed using the Chi-square test or Fisher’s exact test. The survival time and survival curve were determined by Kaplan-Meier survival analysis and compared using the log-rank method. The potential prognostic factors were determined using univariate and multivariate Cox proportional hazard regression models. Prognostic nomogram was established on the basis of the multivariate analyses. The calibration curves were used to assess the predictive performance. Results: The optimal cut-off value for FAR based on the overall survival (OS) was 0.066, as evaluated by the ROC. The 224 included patients were divided into a low (<0.066) and high (≥0.066) FAR groups. Univariate and multivariate models shown that FAR was an potential prognostic factor for disease-free survival (DFS) and OS in patients with TNBC. The median DFS and OS of the low FAR group were longer than those of the high FAR group (χ2=15.080, P=0.0001; χ2=13.140, P=0.0003), including for pre-menopausal patients, and those with pathological stages I+II, and lymph vessel invasion. A nomogram based on the potential prognostic factors was efficient in predicting 3-, and 5-year DFS and OS survival probabilities. Conclusions: The FAR, which is tested routinely and is characterized by its simplicity, objectivity, and inexpensiveness, is a potential prognostic factor of TNBC, and is potentially applicable in clinical practice.